Tables fréquentielles de grec classique, dir. J. Carrière, Besançon, G.R.A.P.E.L.A.B., 1985, 384 pp. ISBN 2-251-60336-0 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Tables fréquentielles de grec classique, dir. J. Carrière, Besançon, G.R.A.P.E.L.A.B., 1985, 384 pp. ISBN 2-251-60336-0